2021
DOI: 10.1371/journal.pone.0257182
|View full text |Cite
|
Sign up to set email alerts
|

Dengue pre-vaccination screening test evaluation for the use of dengue vaccine in an endemic area

Abstract: Background The dengue vaccine (Dengvaxia) is only recommended for individuals with prior dengue infection (PDI). This study aimed to perform a serosurvey to inform decision-making for vaccine introduction and identify appropriate target populations. We also evaluated the performance of the serological tests using plaque reduction neutralization test (PRNT) as a reference test in identifying PDI to determine suitability for pre-vaccination screening. Methods We enrolled 115 healthy individuals between 10 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…8,17 Several RDTs have been suggested as potentially useful tools for pre-vaccination screening; 18 however, evaluations of commercially available RDTs to date have highlighted a need for the development of improved tests, in particular those with higher sensitivity, with evaluations of sensitivity of these tests ranging between 35% and 71%. [10][11][12][13][14]19 In our study, in the indicated age group for CYD-TDV (≥9 years), the new point-of-care OnSite IgG RDT showed high specificity (97%) and high sensitivity (92%); similar results were observed in the age group of participants aged 6 years or older. Therefore, the OnSite IgG RDT might be useful as a point-of-care pre-vaccination screening tool in dengue-endemic areas.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…8,17 Several RDTs have been suggested as potentially useful tools for pre-vaccination screening; 18 however, evaluations of commercially available RDTs to date have highlighted a need for the development of improved tests, in particular those with higher sensitivity, with evaluations of sensitivity of these tests ranging between 35% and 71%. [10][11][12][13][14]19 In our study, in the indicated age group for CYD-TDV (≥9 years), the new point-of-care OnSite IgG RDT showed high specificity (97%) and high sensitivity (92%); similar results were observed in the age group of participants aged 6 years or older. Therefore, the OnSite IgG RDT might be useful as a point-of-care pre-vaccination screening tool in dengue-endemic areas.…”
Section: Discussionsupporting
confidence: 79%
“…10 Other studies have also shown the limitations in sensitivity of currently available RDTs. 11,12 A new dengue IgG-specific RDT, the OnSite Dengue IgG RDT (Onsite IgG RDT; CTK Biotech, Poway, CA, USA), specifically designed for pre-vaccination screening has been developed. In this study, we aimed to assess the efficacy of CYD-TDV in participants of the phase 3 CYD14 and CYD15 studies who were determined to be seropositive to dengue by use of the OnSite IgG RDT and to assess assay performance.…”
Section: Introductionmentioning
confidence: 99%
“… 83 2012–2015 A 0.136 (0.127, 0.146) in-house Thailand Ratchaburi province 10–22 3 115 IgG ELISA Limothai U et al. 84 Aug 2019–Aug 2020 A 0.094 (0.074, 0.118) Bioline, Korea Venezuela Cana de Azucar 05–30 5 2002 Hemagglutination inhibition (HI) Velasco-Salas et al. 85 Aug 2010–Jan 2011 B 0.059 (0.015, 0.181) in-house Vietnam Nha Trang City, Nih Hoa district and Dien Khanh district (in Khanh Hoa province) 03–60 6 1479 indirect IgG ELISA Mai et al.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the cost reduction alone as compared to commercial PMT-based devices may also increase accessibility in centralized locations such as pharmacies, where antibody levels might be recorded during a patient visit to inform on the need for vaccination. For example, in the case of dengue virus, it is particularly relevant to perform pre-vaccination serologic screening [40], suggesting the need for rapid, on-site quantitative patient testing. To increase reproducibility and promote dissemination, we provide a user guide, bill of materials, 3D CAD models, and fully-detailed build guide with instructions.…”
Section: Discussionmentioning
confidence: 99%